(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This study aimed to determine the beneficiaries’ agreement on the impact the social services provided at Bataraza,Palawan. It was conducted in eleven (11)barangays which includes Culandanum,Igang-Igang, Iwahig, Ocayan, Rio Tuba,Sandoval, Sapa, Sarong, Sumbiling, Taratak,and Tarusan with 252 direct recipients using questionnaire as an interview guide. Based on the result of the study, it was found out that majority of the respondents were female, married with an average number of 3 children per family and acquired formal schooling. Almost all of the respondents engaged in farming with an average income of Php6,259.52 per month. The company offered various social services assistance which includes health services, human resource and development and educational assistance which includes numerous programs. Yet, respondents Disagree on the concept that social services improved the way of living of the community. Finally,recipients Slightly Agreed on the statement that a social services create a big impact to their lives and community. Thus, it was recommended that companies and Local Government Unit should conduct an assessment studies to determine the priority needs of the community and prioritize livelihood training and seminars that will enhance the capabilities of the recipients. As to program beneficiaries, they should attend livelihood training and seminars that will enhance their skills and must engage in livelihood activities for additional source of income to uplift the way of living they want.